2018
DOI: 10.1073/pnas.1806002115
|View full text |Cite
|
Sign up to set email alerts
|

Global analysis of mutations driving microevolution of a heterozygous diploid fungal pathogen

Abstract: SignificanceEvolution acts on mutations that naturally arise within the genome and are shaped both by intrinsic genomic features and by the cellular environment. We catalog the mutations arising in a heterozygous diploid yeast during passaging in vitro and in the mammalian host. We establish genome-wide mutation rates and reveal that “microscale” changes (base substitutions and short-track recombination events) are the primary drivers of microevolution, although chromosomal-level changes also occur in specific… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
170
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(194 citation statements)
references
References 102 publications
22
170
0
Order By: Relevance
“…Allelic imbalance 279 in the trisomic strains may also affect cell wall architecture and/or composition, which would then alter 280 immune recognition by the host. Accordingly, the amount of exposed β-glucan on the surface of fungal 281 cells was strongly predictive of competitive fitness in the mouse GI tract (Ene et al 2018). Furthermore, 282 fungal cell wall architecture, rather than cell wall composition, determines the ability of fungi to colonize 283 the GI tract (Sem et al 2016).…”
mentioning
confidence: 99%
“…Allelic imbalance 279 in the trisomic strains may also affect cell wall architecture and/or composition, which would then alter 280 immune recognition by the host. Accordingly, the amount of exposed β-glucan on the surface of fungal 281 cells was strongly predictive of competitive fitness in the mouse GI tract (Ene et al 2018). Furthermore, 282 fungal cell wall architecture, rather than cell wall composition, determines the ability of fungi to colonize 283 the GI tract (Sem et al 2016).…”
mentioning
confidence: 99%
“…The comparison of heterozygosity patterns between different species is often hampered by the use of different methodologies and criteria to define heterozygous and homozygous regions in different studies. For instance, while studies performed so far on C. albicans distinguished heterozygous from LOH regions based on SNP density within windows of 5kb (Ene et al 2018;Wang, Bennett, and Anderson 2018;Hirakawa et al 2015), 10kb (Ropars et al 2018), or even 100kb length (Bensasson et al 2019), studies performed on hybrids defined these blocks based on the distance between heterozygous positions (Pryszcz et al 2014;Pryszcz et al 2015;Mixão et al 2019). This last approach makes the boundaries between heterozygous and LOH blocks more flexible and precise and avoids averaging levels of heterozygosity when a window spans both homozygous and heterozygous regions.…”
Section: Heterozygosity Patterns In C Albicans Are Comparable To Thomentioning
confidence: 99%
“…between different strains (Ropars et al 2018;Wang, Bennett, and Anderson 2018). Furthermore, they have reported that the fraction of the genome covered by heterozygous regions can vary between 48% to 89%, depending on the strain, and that these heterozygous tracts are separated by regions of loss of heterozygosity (LOH) (Ene et al 2018;Ropars et al 2018;Wang, Bennett, and Anderson 2018;Bensasson et al 2019). Moreover, it has been shown that the accumulation of mutations and the exchange of genomic material between strains are the main forces shaping C. albicans genome (Wang, Bennett, and Anderson 2018).…”
mentioning
confidence: 99%
“…While point mutations are quite rare in C. albicans, large-scale genomic rearrangements occur more frequently and are easily detected (Forche et al 2011;Hickman et al 2015;Ene et al 2018). To determine how exposure to antifungal drugs impacts the rate of large-scale rearrangements in diploid and tetraploid C. albicans, we measured the rate of GAL1 loss-ofheterozygosity in both ploidy states.…”
Section: Tetraploid Mutation Rates Are Differentially Impacted By Antmentioning
confidence: 99%